Probiotics, Their Extracellular Vesicles and Infectious Diseases - Domínguez Rubio, A. Paula; D’Antoni, Cecilia L.; Piuri, Mariana; Pérez, Oscar E. (Frontiers in Microbiology, 2022)
Probiotics have been shown to be effective against infectious diseases in clinical trials, with either intestinal or extraintestinal health benefits. Even though probiotic effects are strain-specific, some “widespread effects” include: pathogen inhibition, enhancement of barrier integrity and regulation of immune responses. The mechanisms involved in the health benefits of probiotics are not completely understood, but these effects can be mediated, at least in part, by probiotic-derived extracellular vesicles (EVs). However, to date, there are no clinical trials examining probiotic-derived EVs health benefits against infectious diseases. There is still a long way to go to bridge the gap between basic research and clinical practice. This review attempts to summarize the current knowledge about EVs released by probiotic bacteria to understand their possible role in the prevention and/or treatment of infectious diseases. A better understanding of the mechanisms whereby EVs package their cargo and the process involved in communication with host cells (inter-kingdom communication), would allow further advances in this field. In addition, we comment on the potential use and missing knowledge of EVs as therapeutic agents (postbiotics) against infectious diseases. Future research on probiotic-derived EVs is needed to open new avenues for the encapsulation of bioactives inside EVs from GRAS (Generally Regarded as Safe) bacteria. This could be a scientific novelty with applications in functional foods and pharmaceutical industries.